Development of the youth entrepreneurship: example of Kazakhstan - Zhartay, Zh.; Khussainova, Zh.; Yessengeldin, B. (Entrepreneurship and Sustainability Issues, 2020)
The article deals with the socio-economic analysis of youth entrepreneurship in Kazakhstan. Youth entrepreneurship is defined as a tool to ensure the growth of employment, the involvement of young people in economic activities, their socialization and self-realization. The development of this direction allows to use the creative potential of the younger generation in the interests of innovative development of the country. The author presents the results of socio-economic analysis conducted in the framework of the topic among young entrepreneurs and students of the Republic of Kazakhstan. Published a complex description of the socio-economic subjectivity of youth in Kazakhstan, a systematic analysis of youth entrepreneurship, its quantitative and qualitative parameters, development effectiveness and its impact on the main macroeconomic indicators that characterize the growth of the economy and its innovative flexibility. Received the dynamics of the development of the economically active population of the Republic of Kazakhstan aged 15-28 years according to the indicators presented in the article. Also, the level of youth unemployment and its relationship with the youth category NEET - Not in Education, Employment or Training. The implementation of the common efforts of the state, business, civil society institutions will contribute to the development of youth entrepreneurship is substantiated. The conclusion that only the implementation of common efforts of the state, business, civil society institutions (NGOs) will contribute to the development of youth entrepreneurship is substantiated.
Keywords: youth; entrepreneurship; business activity of youth; startups; young unemployment; young employment; Spearman Coefficient